Application of nuclear-physics methods for studying the radionuclide transport in granite rocks - Dikiy, N.P.; Sayenko, S.Yu.; Uvarov, V.L.; Shevyakova, E.P. (Вопросы атомной науки и техники, 2000)
The results of studying the migration of ¹⁶⁹Yb as actinide-simulator in granite specimens in pristine state and preliminary irradiated with various γ-irradiation dose up to 3,0*10⁹ rad are represented and briefly discussed. Method of γ-spectrometry was used in order to determine the distribution of γ-emitting tracer isotope ¹⁶⁹Yb in granite. Estimations based on analysis of ytterbium bulk distribution are given to determine the diffusion coefficients of radionuclides in granite rock.